Considering Kyai's Transformational Leadership Style for Employee Engagement of Islamic Boarding School Administrators, mediated by Self-Efficacy - Karimah Darojat; Heri Purwanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Islamic boarding school administrators are the determinants of the running of activities at the Islamic boarding school. The service carried out by administrators is generally without material rewards so that their attachment to the management organization is largely determined by the caregivers as the center of Islamic boarding school leadership. Confidence in the management's own abilities is also a supporting factor in carrying out service duties. The method used in this research is a quantitative method, using a transformational leadership style scale, employee engagement scale and self-efficacy scale. The aim of this research is to prove the influence of the transformational leadership style of caregivers as the main leaders on employee engagement of Islamic boarding school administrators, as well as support from the self-efficacy of administrators as a form of readiness in carrying out service duties. The results of this research show that the transformational leadership style significantly influences the employee engagement of Islamic boarding school administrators, F(1,39) = 58.243, P < 0.01 with R2 = 0.599, and this result is stronger when mediated by their self-efficacy. administrator with results F(2,38) = 40.268, P < 0.01 with R2 = 0.679. This means that the transformational leadership style possessed by kyai influences the engagement of Islamic boarding school administrators, this is also supported by the existence of self-efficacy as the administrator's belief in their own ability to carry out their service duties.